Correlation of the stoichiometries of poly(ε-caprolactone) and α-cyclodextrin pseudorotaxanes with their solution rheology and the molecular orientation, crystallite size, and thermomechanical properties of their nanofibers. Issue 112 (23rd November 2016) - Narayanan, Ganesh; Chung, Ching-Chang; Aguda, Remil; Boy, Ramiz; Hartman, Matthew; Mehraban, Nahid; Gupta, Bhupender S.; Tonelli, Alan E.
Abstract : Pseudorotaxane nanofibers based on biomedical polymers, such as poly(ε-caprolactone) (PCL), and α-cyclodextrins (α-CD) open new horizons for a variety of biomedical applications. Abstract : Pseudorotaxane nanofibers based on biomedical polymers, such as poly(ε-caprolactone) (PCL), and α-cyclodextrins (α-CD) open new horizons for a variety of biomedical applications. From our recent report on pseudorotaxane suspensions and nanofibers, we inferred several unique characteristics, such as improvements in mechanical properties and a several-fold increase in viscosity values at low concentrations. In this report, through in-depth characterization employing techniques, such as rheological measurements, we investigate the reasons behind the unusual viscosity values observed in their suspensions. Additionally, combining rheology and TEM, we examine the phenomena responsible for the fiber diameter variation within a single nanofiber. Although, both 2D-wide angle X-ray diffraction patterns and selected area electron microscopy showed poor molecular orientation of the polymer chains along the fiber axis in the pseudorotaxanes, we attribute the observed higher modulus values to the denser nature and crystal packing of the PCL chains emanating from the surfaces of the columnar host α-CD crystals in the pseudorotaxanes, which was evidenced by crystallite size analyses. Finally, dynamic mechanical analyses illustrated that the interlacing of polymer chains protruding from the columnar α-CD cavities have a profound impact on the mechanical properties of these composites.